Periodontal status among 12-year-old schoolchildren: a population-based cross-sectional study in Quito, Ecuador - Marco MEDINA-VEGA; Mariela Cumandá Balseca IBARRA; Maritza Del Carmen QUEZADA-CONDE; Isabella Neme Ribeiro dos REIS; Antonio Carlos FRIAS; Daniela Prócida RAGGIO; Edgard MICHEL-CROSATO; Fausto Medeiros MENDES; Claudio Mendes PANNUTI; Giuseppe Alexandre ROMITO (Sociedade Brasileira de Pesquisa Odontológica, 2024)
Abstract This study aimed to estimate the prevalence and extent of bleeding on probing and calculus in 12-year-old schoolchildren of Quito, Ecuador, and evaluate the associated factors. We conducted an epidemiological survey with a representative sample of 1,100 12-year-old schoolchildren from public schools in the urban area of Quito, Ecuador. We assessed the periodontal health using the Community Periodontal Index (CPI). The prevalence and extent of the periodontal condition was based on the presence of at least one site with bleeding on probing (BOP), and the presence of dental calculus was also evaluated. We used univariate and multiple multilevel Poisson regression analyses to verify the association between the independent variables and the number of sextants with BOP and calculus. The prevalence of BOP and calculus was 92% and 69.9%, respectively. The adjusted mean of the affected sextants was 4.3 and 2.2 for BOP and calculus, respectively. The mother's schooling and malocclusion were associated with the number of sextants with bleeding. The mother's schooling and dental caries experience were associated with calculus. Gingival bleeding and the presence of dental calculus are highly prevalent in 12-year-old schoolchildren from Quito. Gingival bleeding is associated with maternal education and malocclusion, and dental calculus is associated with maternal education and dental caries.